The viral protein corona directs viral pathogenesis and amyloid aggregation: Development of new models and analysis methods: Multisystem platform models of ADRD. (7th December 2020) - Ezzat, Kariem; Malm, Tarja; Gustafsson, Oskar; Lindén, Anders; Andaloussi, Samir E.L.
Abstract: Background: Viruses rely on the intracellular host machinery for replication, production of viral proteins and assembly. However, outside cells, as nanosized obligate intracellular pathogens, viruses share many biophysical properties with nanoparticles. Based on this biophysical equivalence, we hypothesized that viruses accumulate a host‐derived protein corona layer in extracellular environments similar to nanoparticles. Also, like nanoparticles, viruses should be able to function as nanosurface catalysts that enable accelerated amyloid protein aggregation extracellularly. Method: We analyze the protein corona of respiratory syncytial virus (RSV) and herpes simplex virus 1 (HSV‐1) in different biological fluids including human plasma, human bronchoalveolar lavage fluid, non‐human primate plasma, and fetal bovine serum using proteomics, electron microscopy, infectivity and dendritic cell activation assays. In addition, we study the effect of RSV and HSV‐1 on the kinetics of amyloid aggregation of amylodogenic peptides such as amyloid‐beta (Aβ42 ) peptide, which is the major constituent of amyloid plaques in Alzheimer's disease (AD) in‐vitro and in‐vivo in AD animal models. Result: We show that RSV and HSV‐1 accumulate rich protein corona layers that are unique for each biological fluid. Moreover, we show that corona pre‐coating differentially affects viral infectivity and immune cell activation. Additionally, we demonstrate that viruses can bind amyloidogenic peptides in their corona and catalyze amyloid formation via surface‐assisted heterogeneous nucleation. Importantly, we show that HSV‐1, which has been implicated in AD, catalyzes the nucleation and accumulation of the Aβ42 peptide both in‐vitro and in‐vivo . Conclusion: Our results provide a proof‐of‐concept for the presence of an extensive and dynamic viral protein corona layer that is critical for viral‐host interactions. Unlike the viral genome‐coded surface proteins, the viral protein corona is an acquired structural layer that is dependent on the viral microenvironment resulting in different viral identities based on the target tissue and the target organism. Additionally, the demonstration of corona‐driven heterogeneous nucleation of amyloids illustrates convergence between viral and amyloid pathologies suggesting a direct physical mechanistic link that warrants further investigation. Paper: https://www.nature.com/articles/s41467‐019‐10192‐2 .